2021
DOI: 10.1093/eurpub/ckab204
|View full text |Cite
|
Sign up to set email alerts
|

A shift in women’s health? Older workers’ self-reported health and employment settings during the COVID-19 pandemic

Abstract: Background The first wave of COVID-19 has had a massive impact on work arrangements settings in many European countries with potential effects on health that are likely to vary across gender. Methods Focusing on the workforce aged 50 and over in 27 European countries using data from SHARE wave 8 (N = 11,221), the study applies a generalized logit mixed-effects model to assess the relationship between negative and positive cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…Analyses were replicated using self-reported workers' mental health as an outcome. Estimates are of the same nature but with both higher intensities and smaller confidence intervals, indicating a stronger perceived change in mental health during the pandemic, as documented by previous studies for the global population (Patel et al, 2022) as well as for the workforce (Wels & Hamarat, 2021). Results in table 3 show a positive and statistically significant association between reporting a worse social dialogue and a poorer self-reported perceived physical health of the workers (RR:1.40, 95%CI= 1.11; 1.78) in the non-adjusted model.…”
Section: [Please Insert Table 2]supporting
confidence: 69%
“…Analyses were replicated using self-reported workers' mental health as an outcome. Estimates are of the same nature but with both higher intensities and smaller confidence intervals, indicating a stronger perceived change in mental health during the pandemic, as documented by previous studies for the global population (Patel et al, 2022) as well as for the workforce (Wels & Hamarat, 2021). Results in table 3 show a positive and statistically significant association between reporting a worse social dialogue and a poorer self-reported perceived physical health of the workers (RR:1.40, 95%CI= 1.11; 1.78) in the non-adjusted model.…”
Section: [Please Insert Table 2]supporting
confidence: 69%
“…The existing studies on subsidised employment show inconsistent, although mostly beneficial effects on health and wellbeing (Puig-Barrachina et al, 2020; Wels & Hamarat, 2021). For example, focusing on the restaurant industry in the US using cross-sectional data, Bufquin et al (2021) showed that working employees experienced higher levels of psychological distress, drug, and alcohol use than temporary unemployed workers.…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive statistics during the Covid-19 pandemic have shown that home working was associated with positive experiences in terms of housework and childcare responsibilities, both for men and women, but the flip side of it was that homeworking was perceived as blurring the boundaries between work and family life 3) . In line with this, it was shown that homeworking arrangements had a positive relationship with the older workforce's self-reported health in the early stage of the pandemic, but that men's health benefited more from those arrangements than women 19) . Prevalence of depression, anxiety, and stress among remote workers is indeed affected by sex, and a higher increase in both housework and working hours during the COVID-19 pandemic has been observed among women compared with men 20) , as well as a greater decline in mental health amongst women.…”
Section: Introductionmentioning
confidence: 68%
“…Mental health differences by age and sex have been constantly observed 44) and both differences have widened during the pandemic 45) but independently of labour market positions or the type of employment arrangement 19,46) . We find that younger cohorts or age groups have been reporting lower life satisfaction (except in Usoc), higher anxiety, higher depression and higher psychiatric distress compared with older cohorts or age groups throughout the pandemic.…”
Section: Discussionmentioning
confidence: 99%